Decision support in Down’s syndrome screening using multi-criteria decision analysis: a pilot study - Anna Erenbourg; Judith Stephenson; Pranav Pandya; Patricia Jones; Jack Dowie (Epidemiology, Biostatistics and Public Health)
Background: the aim of the study was to develop and pilot use of a decision support system (DSS) to help women choose the option that best respects their personal values among the different screening/diagnostic tests for Down’s syndrome. Methods: value-bearing considerations were elicited through qualitative interviews. Ten women post-birth and ten health professionals working in the Obstetric Department at UC LH were interviewed. Performance data for the various possible screening strategies on these attributes were entered into a Multi-criteria Decision Analytic model using the Annalisa implementation. Participants piloted the DSS, entering necessary weights for the attributes and observing the resulting scores. Main outcome measures were DSS clarity, usefulness and feasibility in a clinical setting. Results: most participants found the DSS valuable because it stimulated women to seek information about testing and helped them focus on the main issues affecting their decisions. Annalisa proved a user-friendly DSS that helps women understand the issues around Down’s screening and diagnosis. There was unanimity that its use should be complementary to health professionals’ consultation. Most favoured offering it before consultation so that women could be better informed about options before attending the antenatal booking. Conclusions: the overall positive comments confirm that a user-friendly decision analysis-based support system can be a valuable instrument at supporting health decisions in this area. Further research is needed to assess whether the intention to make an informed choice is always best addressed by a decision support system, or these remain useful tools only to women more inclined to seek information anyhow.